LEKSIKON ETNOMEDISIN PADA PENGOBATAN PENYAKIT KULIT MELAYU SUKADANA: KAJIAN EKOLINGUISTIK - Mellisa Jupitasari (Universitas Andalas, 2021)
This research aims to describe the etnomedicine lexicon in skin illness theraphy of Sukadana Malay.The etnomedicine lexicon in skin illness theraphy of Sukadana Malay includes lexicons of Sukadana Malay skin illness's names, lexicons of herb's names that are used to heal Sukadana Malay skin illness and lexicons of the way of healing Sukadana Malay skin illnes. This research uses a descriptive qualitative method and uses an ecolinguistic study approach to analyze the ethnomedicin lexicon in the treatment of Sukadana Malay skin disease. The source of data is the interview result from the informant ( Sukadana Malay citizen) about etnomedicine lexicon in skin illness therapy of Sukadana Malay. The result of the research gathers 22 lexicons of Sukadana Malay skin illness's names, 39 lexicons of herb's names that are used to heal Sukadana Malay skin illness and 9 lexicons of the way of healing Sukadana Malay skin illness.